Indonesia’s 2024 Election: Constitutional Court Perspectives on Electoral Violations - A Zarkasi; Firmansyah Putra; Dinda syufradian Putra; Farhanin binti Abdullah Asuhaimi (Sriwijaya Law Review, 2025)
In 2024, Indonesia held a historic general election in which, for the first time, presidential, vice-presidential, and legislative elections were conducted simultaneously across all regions of the country. However, the election was marred by indications of various violations that raised concerns about its integrity. This study investigates violations that occurred during Indonesia’s 2024 general elections by analysing Constitutional Court rulings on electoral disputes. Employing a qualitative case study approach supported by NVivo 12 Plus for data analysis, the research identifies key institutional actors involved in the disputes, including the General Election Commission, the Election Supervisory Body, political parties, and other stakeholders. The findings categorize electoral violations into three major types: administrative, ethical, and criminal. Administrative violations are largely attributed to procedural complexities, inadequate preparation, and limited time for implementation, leading to errors in electoral management. Ethical violations arise from misconduct by election officials and political actors, often breaching the standards outlined in the Indonesian Electoral Law. Criminal violations, the most severe, include state apparatus interference, vote-buying, and voter disenfranchisement, all of which severely compromise electoral integrity and democratic principles. These violations have resulted in significant legal consequences, such as mandated re-voting in specific regions, vote recounts, and the disqualification of candidates. The study highlights systemic weaknesses in Indonesia’s electoral governance and underscores the urgent need for institutional reforms to ensure fair, transparent, and accountable electoral processes. Ultimately, the research contributes to a deeper understanding of the challenges facing democratic consolidation in Indonesia and the legal mechanisms available to address electoral disputes.